MÔ PHỎNG QUÁ TRÌNH LAN TRUYỀN VÀ BIẾN ĐỔI VỆT DẦU TRÊN BIỂN ĐÔNG BẰNG MÔ HÌNH TOÁN - Công, Lê Văn; Sáo, Nguyễn Thọ; Thành, Nguyễn Trung; Thành, Nguyễn Quang (Vietnam Journal of Earth Sciences, 2011)
Simulation of the oil transporting and weathering processes in the Bien Dong by numerical modelsOil spill in the Bien Dong which often occurs, has a great influence on eco-environment and socio-economic development of coastal areas of Vietnam. However, most of reasons of oil spill were unknown, especially offshore oil spill, and it is very difficult to apply proper measures.There were several published works in Vietnam concerning oil spill [1, 4-7], but the problems are mainly in nearshore zones and fully based on assumption of marine hydro-meteorological and oil spill conditions. These problems were solved using either Remote Sensing or Numerical Models.This article presents the predicted results of two oil spill traces (2 scenarios) occurred in the Bien Dong. It is the first time these problems are solved by combining methods in Remote Sensing with Numerical Modeling methods. The oil specification parameters such as location, quantity, oil type. etc., were considered as input to Numerical Models, which were processed and analyzed from the satellite images ALOS PALSAR using Remote Sensing Interpretation. All hydrometeorologicalinput data are actual figures determined at the time of oil traces. Propagation of oil spills are considered to be useful and can be used as forecasts for similar situations.This article is supported by National Science and Technology Project, Code KC.09/06-10/22: "Oil spill in the Bien Dong and Vietnamese Sea".